2020
DOI: 10.1186/s40942-019-0204-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal ziv-aflibercept in diabetic vitreous hemorrhage

Abstract: Background: To evaluate the safety and efficacy of intravitreal ziv-aflibercept (IVZ) in the management of vitreous hemorrhage (VH) in eyes with previously lasered proliferative diabetic retinopathy (PDR). Methods:In a prospective multicenter study, previously lasered eyes who had dense VH from PDR underwent intravitreal injection of ziv-aflibercept (IVZ) (1.25 mg aflibercept). Demographic characteristics of the patients, baseline and final logMar visual acuity, number of injections, VH clearance time, and nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The literature search yielded 774 articles, of which 6 were eligible for inclusion. A full-text review identified four articles to be excluded (one uncontrolled study, 15 one study in which IVA was compared to sham treatment, 16 and two studies in which IVA was compared with PRP) 10 , 17 , and ultimately, only two articles were included in the qualitative and quantitative synthesis. The PRISMA flowchart for the selection of studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 774 articles, of which 6 were eligible for inclusion. A full-text review identified four articles to be excluded (one uncontrolled study, 15 one study in which IVA was compared to sham treatment, 16 and two studies in which IVA was compared with PRP) 10 , 17 , and ultimately, only two articles were included in the qualitative and quantitative synthesis. The PRISMA flowchart for the selection of studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite vision improvement reported in approximately 75% of PDR patients after PPV, major complications associated with PPV include cataract formation, elevated intraocular pressure, recurrent vitreous cavity haemorrhage (early, delayed, or persistent), iatrogenic retinal breaks, tractional and rhegmatogenous retinal detachment, and neovascular glaucoma[ 109 ]. Several studies have been conducted on the use of anti-VEGF drugs as a treatment for VH due to PDR and found that intravitreal ranibizumab[ 110 ], bevacizumab[ 111 , 112 ], and aflibercept[ 113 ] had good short-term safety and efficacy for new or recurrent VH in PDR eyes with and without a previously lasered approach, reducing the need for PPV. As the use of anti-VEGF drugs is associated with pregnancy loss and foetal abnormalities, PRP and PPV remain the treatment of choice for VH in pregnant patients with PDR.…”
Section: Preparing For Dr Progression In Pregnant Diabeticsmentioning
confidence: 99%
“…To mention, Ahmad M. Mansour et al . [ 8 ] studied the effects of ziv-aflibercept on VH in eyes with PDR status post pan-retinal photocoagulation and found its beneficial effects for the therapy of VH.…”
mentioning
confidence: 99%